Problems of ICD-10 coding in health information systems using the example of coronary artery disease - Samorodskaya, I. V.; Kakorina, E. P.; Klyuchnikov, I. V. (Rossiĭskiĭ kardiologicheskiĭ zhurnal, 2025)
Aim. To assess the possibilities and problems of using health information systems (HIS) to record disease cases and causes of death using ICD-10 codes using coronary artery disease (CAD) forms as an example. Material and methods. The study combined data from electronic databases of the Main Civil Registry Office and outpatient clinics of the Moscow Oblast. All cases with CAD codes registered as the underlying cause of death (UCD) in outpatient clinics and in medical certificates of cause of death (MCCD) one year before death were included. A total of 3476 deaths. Results. On average, 1,4 four-digit ICD codes from the CAD group (I20-I25) per patient were registered in outpatient clinics per year. More than 1 code from the CAD group was registered in 33,3% of patients. For one conditional disease (CAD), 86 unique consecutive combinations of 4-digit CAD codes were identified, which indicates the changes of the patient's condition over time. Myocardial infarction (MI) as a UCD is indicated in 12,1% of the MCCD (9,1% — I21 and 3% — I22); in 83,9% — one of 7 codes of the chronic forms of CAD group (I25.0, 1, 2, 3, 5, 8, 9). Among those who had only codes of the chronic forms of CAD group (I25) indicated in outpatient clinics, 9,6% died of MI. The problems associated with the use of codes for creating registers and their subsequent clinical interpretation are described. In addition to CAD codes, other diseases represented by 4-digit codes (on average, 6,0±4,9 per patient) were registered in the outpatient clinics in 90,7% of patients. Causes of death (Part II of the MCCD) were indicated in 24,3%. Conclusion. HIS have significant potential for accumulation and subsequent clinical analysis of data, but for full use, expert approval of the criteria for applying codes for various clinical forms of CAD is required.